A BUSINESS MODEL FRAMEWORK FOR INTERNET OF THINGS (Journal of Engineering and Health Sciences, 2019)
The Internet of Things (IoT) generates new business opportunities by connecting physical objects with a multitude of sensors. IoT research mainly focused on technology and business models are relatively unexplored, although developing IoT business models is important for successful IoT service. This study aims to investigate what are the elements to be taken in order to create a business model for IoT. To address this issue, we review the literature on the creation of business model for IoT and propose a generic business model framework for IoT business through the literature analysis. The IoT allows existing business models to change and new business to emerge. This research acts as a starting point for designing or developing business models for IoT services.